Codiagnosability of Networked Discrete Event Systems With Timing Structure - Viana, Gustavo S.; Alves, Marcos V. S.; Basilio, Joao Carlos (IEEE transactions on automatic control, 2022)
We address, in this article, the problem of codiagnosability of networked discrete event systems with timing structure (NDESWTS) subject to delays and loss of observations of events between the measurement sites (MS) and local diagnosers (LD). To this end, we first introduce a new timed model that represents the dynamic behavior of the plant based on the, a priori , knowledge of the minimal activation time for each transition of the plant and on the maximal delays in the communication channels that connect MS and LD. We then convert this timed model into an equivalent untimed one, and add possible intermittent packet loss in the communication network. Based on this untimed model, we present necessary and sufficient conditions for NDESWTS codiagnosability and propose two tests for its verification: one that deploys diagnosers and another one that uses verifiers.